Mortars modified with geothermal nanosilica waste: effect on the electrochemical properties of embedded steel rods - Puente Ornelas, Rodrigo; Gómez Zamorano, Lauren Yolanda; Alonso, M.C.; Zambrano Robledo, Patricia del Carmen; Guzmán Hernández, Ana María; Rodríguez, E. A.; Bermúdez Reyes, Bárbara; Sánchez Moreno, M. (Electrochemical Science Group, 2012)
Nowadays, it is a common practice the incorporation of industrial wastes as alternative materials to replace ordinary Portland cement in the concrete manufacture. This technological implementation has as main objectives, the enhancement of concretes properties as well as mitigation of durability problem related to the corrosion phenomena; in order to increase the service life of reinforced concrete structures. Therefore, in this research was studied the electrochemical properties of black steel embedded in mortars. Mortars were fabricated using as a partial substitute of cement (0, 10, 20 and 30 wt. %) a geothermal nanosilica waste composed of amorphous nanosilica of ~20ηm and chlorides (0 and 0.4 wt. %). Mortars were subjected to a cure at 20°C (80% of relative humidity) and 60ºC (100% of relative humidity). The corrosion behaviour was periodically monitorized up to 65 days using electrochemical techniques of corrosion potential (Ecorr) and corrosion current density (icorr). Values of current density (icorr) were obtained by linear polarization resistance (LPR) technique applying Stern-Geary relation to Rp values. Electrochemical results were validated by comparing with gravimetric losses. The porosity, pH and loss of the evaporated water were also evaluated in mortars. Results obtained showed that the integrity of reinforcement rods was affected with the increase of GNW at high temperatures as well as the total chlorides content in mortars.